Disentangling the effects of spring anomalies in climate and net primary production on body size of temperate songbirds. Issue 8 (28th February 2018) - Dubos, Nicolas; Le Viol, Isabelle; Robert, Alexandre; Teplitsky, Céline; Ghislain, Manon; Dehorter, Olivier; Julliard, Romain; Henry, Pierre Yves
Abstract : Body size is implicated in individual fitness and population dynamics. Mounting interest is being given to the effects of environmental change on body size, but the underlying mechanisms are poorly understood. We tested whether body size and body condition are related to ambient temperature (heat maintenance hypothesis), or/and explained by variations in primary production (food availability hypothesis) during the period of body growth in songbirds. We also explored whether annual population‐level variations of mean body size are due to changes of juvenile growth and/or size‐dependent mortality during the first year. For 41 species, from 257 sites across France, we tested for relationships between wing length (n = 107 193) or body condition (n = 82 022) and local anomalies in temperature, precipitation and net primary production (NDVI) during the breeding period, for juveniles and adults separately. Juvenile body size was best explained by primary production: wings were longer in years with locally high NDVI, but not shorter in years with low NDVI. Temperature showed a slightly positive effect. Body condition and adult wing length did not covary with any of the other tested variables. We found no evidence of climate‐driven size‐dependent mortality for the breeding season. In our temperate system, local climatic anomalies explained little of the body size variation. A large part of wing length variance was site‐specific, suggesting that avian size was more dependent on local drivers than global ones. Net primary production influenced juvenile size the most through effects on body growth. We suggest that, during the breeding season in temperate systems, thermoregulatory mechanisms are less involved in juvenile growth than food assimilation.